First record of the non-native Cnestus mutilatus (Blandford) and further findings of other Xyleborini (Curculionidae, Scolytinae) recently recorded in Slovenia - Hauptman, Tine; Capuder, Luka; Devetak, Zina; Groot, Maarten De; Faccoli, Massimo; Piškur, Barbara (Zootaxa, 2025)
Ambrosia beetles of the subfamily Scolytinae (Coleoptera: Curculionidae) have successfully invaded many parts of the world and are increasingly being introduced to new areas, primarily through international trade. The number of non-native species recorded in Slovenia is also increasing. During the national survey of quarantine species in 2024, a new non-native scolytine beetle, Cnestus mutilatus, was recorded for the first time in Slovenia. Two specimens were trapped at Radmožanci, a location in northeastern Slovenia. New data on two other species recently recorded in Slovenia, Anisandrus maiche and Xylosandrus compactus, are also presented.